Observations on the Feeling of the Beautiful and Sublime - Kant, Immanuel 1724-1804 (Berkeley University of California Press, 1960)
When originally published in 1960, this was the first complete English translation since 1799 of Kant's early work on aesthetics. More literary than philosophical, Observations shows Kant as a man of feeling rather than the dry thinker he often seemed to readers of the three Critiques.